ANALISIS SEMIOTIKA SOSIAL OBJEK MATERIAL DALAM CERPEN KOTA SERIBU TAFSIR KARYA MULLA SHANDRI: PERSPEKTIF WEBB KEANE - Taswirul Afkar; Amy Krisdiana; Wiwik Mardiana (Indonesian language and literature education program Majapahit Islamic University, 2025)
This study aims to analyze the short story City of a Thousand Interpretations by Mulla Shandri using Webb Keane's social semiotic framework. The research employs qualitative descriptive methods with semiotic analysis approach. Research data consists of linguistic units containing semiotic signs in the short story. Results indicate: (1) iconicity is represented through symbolic objects such as the silver peacock, olive wood gate, and ancient manuscript representing plurality values and meaning ambiguity; (2) indexicality appears in causal relationships between the ancient manuscript and Sofyan's dimensional transfer, and cracks in the peacock as index of diversity value degradation; (3) semiotic ideology presents conflict between